Modification of polymers with the application of ion beam bombardment. Part II. Modification of functional properties of rubber - Ostaszewska, U.; Pieczyńska, D.; Bieliński, D. M.; Jagielski, J. (Polimery, 2012)
The surface of rubbers: natural (NR), styrene-butadiene (SBR) and acrylonitrile-butadiene (NBR) or its mixes with chloroprene rubber (NBR/CR) were subjected to high-energy He+, O+, Ar+ or F+ ion beam treatment. Based on the changes in the chemical composition and physical structure of rubber macromolecules in the surface layer and on the surface geometry of ion-irradiated materials, the effect of this modification on the functional properties of the vulcanizates was evaluated. Interactions between high energy ion beam and macromolecules are of elastic character (resulting in an ionization with release of hydrogen — Fig. 1), or inelastic, leading to the degradation of polymer. Graphitization, together with an increased degree of crosslinking of the surface layer, result in an increase in the microhardness of the rubber subjected to ion bombardment (Fig. 2). The shrinkage associated with higher crosslinking of the material causes the formation of a microcrack network on the vulcanizate surface (Fig. 3). The oxidation (Table 2) and the increased surface roughness, change the wettability of rubber surface (Fig. 7) and the friction (Fig. 4), while the polarization and surface development increase the adhesion (Table 3) and bacteriostaticity (Table 6) of the modified vulcanizates. The rubber surface layer subjected to ion bombardment can play a role of a protective barrier, which prevents the inside of material from the action of various chemical or biological factors. As a result of the modification, the rubber becomes more resistant to ageing (both thermal and ozone — Fig. 9), exhibits improved thermal stability (Table 4) and reduced flammability (Table 5) as well as the increased resistance to fuel (Fig. 10) and bacteria.